2020
DOI: 10.1016/j.fuel.2019.116334
|View full text |Cite
|
Sign up to set email alerts
|

Shape and size transformations of biomass particles during combustion

Abstract: This is a repository copy of Shape and size transformations of biomass particles during combustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Infrared thermographics can be used for the measurement of the surface temperature of burning biomass particles. 129 However, the determination of the emissivity of the particle may introduce an uncertainty in the temperature measurement. Using two adjacent wavelengths, λ 1 and λ 2 , eq 2 can be rewritten as…”
Section: ■ Recent Development In Numerical Modeling Of Biomass Conver...mentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared thermographics can be used for the measurement of the surface temperature of burning biomass particles. 129 However, the determination of the emissivity of the particle may introduce an uncertainty in the temperature measurement. Using two adjacent wavelengths, λ 1 and λ 2 , eq 2 can be rewritten as…”
Section: ■ Recent Development In Numerical Modeling Of Biomass Conver...mentioning
confidence: 99%
“…Thus, the particle surface temperature can be obtained based on the analysis of the thermal radiation spectrum. Infrared thermographics can be used for the measurement of the surface temperature of burning biomass particles . However, the determination of the emissivity of the particle may introduce an uncertainty in the temperature measurement.…”
Section: Optical Studies Of Single Biomass Particle/pellet Conversionmentioning
confidence: 99%
“…Thus, the average volume of particles can be calculated by the aspect ratio and the average semiminor axis. During gasification, the particle can shrink, its shape might change, and particle fragmentation may also happen. , The effect of particle shrinkage will be separately discussed in Subsection . Pereira and Pinho experimentally investigated the impact of particle fragmentation on the kinetic and diffusive data for biochar fluidized-bed combustion.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…They found that the kinetic and diffusive data were overestimated by 10% and 5%, respectively, when not considering the particle fragmentation. Riaza et al revealed that nonspherical particles could take on a nearly spherical shape during the conversion. However, the particle fragmentation and shape change are not considered in this work due to the immaturity of the submodels.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…29 A woody material and biomass particle combustion has been carried out using a rapid-heating device. 30 A highspeed camera was used to capture the successive combustion processes. The images demonstrated the sequential burning of volatile materials, followed by the burnout of the leftover char.…”
Section: Introductionmentioning
confidence: 99%